An experimental model for studying the biomechanics of embryonic tendon: Evidence that the development of mechanical properties depends on the actinomyosin machinery - Kalson, Nicholas S. (Elsevier, 2010)
Tendons attach muscles to bone and thereby transmit tensile forces during joint movement. However, a detailed understanding of the mechanisms that establish the mechanical properties of tendon has remained elusive because of the practical difficulties of studying tissue mechanics in vivo. Here we have performed a study of tendon-like constructs made by culturing embryonic tendon cells in fixed-length fibrin gels. The constructs display mechanical properties (toe–linear–fail stress–strain curve, stiffness, ultimate tensile strength, and failure strain) as well as collagen fibril volume fraction and extracellular matrix (ECM)/cell ratio that are statistically similar to those of embryonic chick metatarsal tendons. The development of mechanical properties during time in culture was abolished when the constructs were treated separately with Triton X-100 (to solubilise membranes), cytochalasin (to disassemble the actin cytoskeleton) and blebbistatin (a small molecule inhibitor of non-muscle myosin II). Importantly, these treatments had no effect on the mechanical properties of the constructs that existed prior to treatment. Live-cell imaging and (14)C-proline metabolic labeling showed that blebbistatin inhibited the contraction of the constructs without affecting cell viability, procollagen synthesis, or conversion of procollagen to collagen. In conclusion, the mechanical properties per se of the tendon constructs are attributable to the ECM generated by the cells but the improvement of mechanical properties during time in culture was dependent on non-muscle myosin II-derived forces.